The Impact of Exchange Rate Volatility on International Trade: Evidence from China - Anis, Marwa; AlaaElDin, Aya (The Arab Journal of Administration, 2023)
This paper proposes helpful insights regarding the impact of the exchange rate volatility on international trade. The focus has been on China using a monthly data from the period of January 2003 to August 2018. This is mainly an attempt to contribute to the ongoing debates about this relationship. Time series analysis is adopted specifically; stationary test, granger-causality test, co-integration and error correlation model and finally the residual test. Results indicate that there is a co-integration relationship among the variables. The error correlation model has shown that both the exchange rate and inflation have a significant negative impact on imports. Additionally, there is a significant positive relationship between the exchange rate and exports. Further results have shown there is a significant negative relationship between inflation and exports. A few suggestions are provided to the Chinese policy makers. In this connection, a guideline for future researchers are presented.